Nanocarriers: a versatile approach for mucosal vaccine delivery. (February 2015) - Mody, Nishi; Sharma, Rajeev; Agrawal, Udita; Vyas, Suresh P
Infectious agents generally use mucosal surfaces as entry port to the body thereby necessitating the need of development of mucosal vaccine as vaccination is important for disease avoidance and suppression. Vaccination through mucosal route is a promising strategy to elicit efficient immune response as parentally administered vaccines induce poor mucosal immunity in general. Safety, economy and stability are highly desired with vaccines and this can be achieved with use of delivery cargos. This review focuses on challenges related with mucosal vaccines and use of nanocarriers as suitable cargos to cater the antigen effectively to the desired site. The review also includes different factors which are to be considered regarding the performance of the nanocarriers and clinical status of these systems.